2015
DOI: 10.1016/j.lindif.2015.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Will not want: Self-control rather than motivation explains the female advantage in report card grades

Abstract: Girls earn better grades than boys, but the mechanism explaining this gender difference is not well understood. We examined the relative importance of self-control and motivation in explaining the female advantage in grades. In Study 1, we surveyed middle school teachers and found they judged girls to be higher in both school motivation and self-control. In Studies 2 and 3—using self-reported motivation and teacher- and/or parent-reported self-control, and quarterly and final grades obtained from school record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 65 publications
5
29
0
2
Order By: Relevance
“…Interestingly, we also find that task-based goals were more e↵ective for male students than for female students, both in terms of the impact on the number of practice exams completed and on performance in the course. This finding is consistent with evidence from other educational environments that suggests that males have less self-control than females (e.g., Duckworth and Seligman, 2005, Buechel et al, 2014, and Duckworth et al, 2015 and with Duckworth et al (2015)'s conjecture that educational interventions aimed at improving self-control may be especially beneficial for males.…”
Section: Introductionsupporting
confidence: 89%
“…Interestingly, we also find that task-based goals were more e↵ective for male students than for female students, both in terms of the impact on the number of practice exams completed and on performance in the course. This finding is consistent with evidence from other educational environments that suggests that males have less self-control than females (e.g., Duckworth and Seligman, 2005, Buechel et al, 2014, and Duckworth et al, 2015 and with Duckworth et al (2015)'s conjecture that educational interventions aimed at improving self-control may be especially beneficial for males.…”
Section: Introductionsupporting
confidence: 89%
“…These include counselors and mentors, campus centers that students can visit, and student success programs and courses that students are encouraged 41 Existing empirical evidence supports the idea that men are more present biased than women. In the introduction we referred to evidence from educational environments that females have more self-control than males (e.g., Duckworth and Seligman, 2005, Buechel et al, 2014, and Duckworth et al, 2015. Consistent with gender differences in self-control, incentivized experiments suggest that men may be more present biased than women.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it might be fruitful to go beyond the domain‐specific focus of the expectancy‐value model and explore the importance of the variables included in this study relative to variables found to be important for scholastic success in general. Girls’ better achievement at school in general has been linked to the existence of gender differences in a variety of skills (e.g., self‐control; Duckworth et al ., ) and personality traits (e.g., agreeableness; Steinmayr & Kessels, ) which are related to grades at school, and to a better fit between the culturally shared conception of femininity (as compared to masculinity) and academic demands (e.g., Kessels & Steinmayr, ; Kessels et al ., ). Further, situational factors like stereotype threat (regarding the stereotype that boys are academically inferior to girls) were found to decrease boys’ achievement in several subjects (Hartley & Sutton, ).…”
Section: Discussionmentioning
confidence: 99%